Students’ Perception About Intercultural Competence (IC) in English Speaking Class - Mite, Maria Kristina; Binawan, Heribertus (Pusdikra-Publishing.com, 2025)
This research aims to find out students' views on intercultural competence in learning English speaking. This competence is seen as a fundamental aspect in building effective cross-cultural communication, especially in the context of foreign language learning. The research utilized mixed methods, involving 30 second semester students from Universitas Mercu Buana Yogyakarta who were enrolled in Speaking course. Data collection was conducted through an intercultural competence questionnaire, semi-structured interviews in Focus Group Discussions, direct classroom observations, as well as open-ended questions.From the quantitative results, it was found that students have a high level of cultural awareness and openness, but their cultural knowledge and cross-cultural communication skills are still classified as moderate to low. Meanwhile, qualitative data analysis showed that students understood the importance of cultural insights to support speaking skills, but they felt that the learning process had not fully supported the development of intercultural competence optimally.Based on these findings, this study recommends that cultural elements be integrated more deeply in the teaching of speaking, so that students can be better prepared to face the challenges of global communication. The findings of this study are expected to be a reference in the development of intercultural competence-based English language learning curriculum in higher education.